2022
DOI: 10.1155/2022/4069778
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility Analysis of 3D Printing-Assisted Pedicle Screw Correction Surgery for Degenerative Scoliosis

Abstract: Objective. To explore the feasibility of 3D printing-assisted pedicle screw correction surgery for degenerative scoliosis. Methods. From January 1, 2015 to January 31, 2020, patients with degenerative scoliosis who received corrective surgery in our hospital were retrospectively analyzed. Patients were grouped based on the fixation methods. Patients in the control group received traditional pedicle screw internal fixation, while those in the study group received 3D printing-assisted pedicle screw fixation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%